Fatigue crack growth simulation of two non-coplanar embedded cracks using s-version finite element method - Akiyuki Takahashi; Ayaka Suzuki; Masanori Kikuchi (Fracture and Structural Integrity)
In this paper, the fatigue crack growth simulation of two non-coplanar embedded cracks using the s-version finite element method is presented, and the validity and reliability of the alignment rule for two non-coplanar cracks are evaluated. According to the previous numerical and experimental studies on two non-coplanar surface cracks, the simulated fatigue crack growth behavior is categorized into five patterns to discuss the criteria for the application of the alignment rule. The results suggest that the strength of interaction between the non-coplanar embedded cracks is similar to that between non-coplanar surface cracks. Finally, the interaction of the cracks is evaluated by the stress intensity factor, and the categorization of the fatigue crack growth behavior is discussed by the stress intensity factor. It can be found that the boundary corresponding to the criteria of the application of the alignment rule can be determined as the ratio of the stress intensity factor is 4%. Thus, instead of making a decision of the fatigue crack growth pattern based on the visual inspection, the ratio of the stress intensity factor can be used, and should give more quantitative evaluation of the interaction of two non-coplanar embedded cracks.